An efficient method of sorting liver stem cells by using immuno-magnetic microbeads - He, Yu-Fei (Baishideng Publishing Group Co., Limited, 2006)
AIM: To develop a method to isolate liver stem cells fast and efficiently. METHODS: Fetal mouse liver cells were characterized by cell surface antigens (c-Kit and CD45/TER119) using flow cytometry. The candidate liver stem cells were sorted by using immuno-magnetic microbeads and identified by clone-forming culture, RT-PCR and immunofluorescence assays. RESULTS: The c-Kit(–)(CD45/TER119)(–) cell population with 97.9% of purity were purified by immuno-magnetic microbeads at one time. The yield of this separation was about 6% of the total sorting cells and the cell viability was above 98%. When cultured in vitro these cells had high clone-forming and self-renewing ability and expressed markers of hepatocytes and bile duct cells. Functionally mature hepatocytes were observed after 21 d of culture. CONCLUSION: This method offers an excellent tool for the enrichment of liver stem cells with high purity and viability, which could be used for further studies. It is fast, efficient, simple and not expensive.